Effects of Cadmium Chloride on the Activity ofFour Enzymes in Gills of Mosquito FishGambusia affinis - Waad S. Shahir (College of Education for Pure Sciences, 2007)
Abstract : Gambusia affinis fishes were exposed to 2,4 and 8 mg Cd/L of water for 8 days and for 2,4, and 8 days to 10 mg Cd/L of water. Gills were used to investigate the effect of cadmium on the activity of four enzymes measured by calorimetric methods. There were no clear changes in the activity of Alkaline phosphatase at different concentrations but the activity increased at different periods of exposure to cadmium. Acid phosphatase activity showed a gradual inhibition after the first concentration, while the activity increased at the different periods. There was no change in the activity of aspartate aminotransferase (AST) at different concentrations and periods of exposure. Alanine aminotransferase (ALT) activity increased at the concentrations 2 and 8 mg Cd/L, but the activity increased after the first period and decreased gradually at other periods of exposure to the metal.